A Novel Parasitic, Syndinean Dinoflagellate Euduboscquella triangula Infecting the Tintinnid Helicostomella longa - Choi, Jung Min; Jung, Jae Ho; Kim, Ki Hong; Coats, D. Wayne; Kim, Young Ok (Frontiers in Marine Science, 2021)
A tintinnid species, Helicostomella longa, infected by the parasitic dinoflagellate Euduboscquella triangula n. sp. was discovered from the southern coast of Korea in August of 2015 and 2016. Parasite morphology and development were analyzed by observation of live cells and protargol-stained specimens. The parasite was determined to be a new species in the genus Euduboscquella based on morphological and molecular data. A representative sequence of the novel species clustered in Euduboscquella group I. The morphological and developmental features of E. triangula were distinguished from those of its congeners by: (1) numerous shallow and intertwining grooves on an inconspicuous shield; (2) sporocytes initially forming a short chain, but separating after the second or third division regardless of spore type; (3) production of motile mushroom-shaped dinospores, non-motile spherical spores, and non-motile triangular spores. Dinospores were formed by ca. 28% of infections, while both non-motile spherical and triangular spores occurred at a frequency of ca. 36%. All spore types showed completely identical 18S rDNA sequences. Parasite prevalence was 15.5% and 8.3% on 17 and 24 August of 2015, respectively, with infection intensity on both dates being 1.3.